Health care professionals’ knowledge, attitudes and practices relating to umbilical cord blood banking and donation: an integrative review - Peberdy, Lisa (BMC Pregnancy Childbirth, 2016)
BACKGROUND: Collection and storage of an infant’s cord blood at birth is an option available to many new parents. Antenatal health care providers have an important role in providing non-biased and evidence based information to expectant parents about cord blood and tissue banking options. The aim of this paper was to identify and review studies of health care professionals’ knowledge, attitudes and practices concerning cord blood banking and the sources by which healthcare professionals obtained their information on this topic. METHODS: An integrative review was conducted using several electronic databases to identify papers on health care professionals’ knowledge, attitudes and practices pertaining to cord blood banking. The CASP tool was used to determine validity and quality of the studies included in the review. RESULTS: The search of the international literature identified nine papers which met review inclusion criteria. The literature review identified that there was little focus placed on antenatal health care professionals’ knowledge of cord blood banking options despite these health care professionals being identified by expectant parents as their preferred, key source of information. CONCLUSION: Limited high quality studies have investigated what health care professionals know and communicate to expectant parents regarding cord blood banking. Further research should focus on understanding the knowledge, attitudes and practices of healthcare professionals and how they communicate with expectant parents about this issue. In addition, how this knowledge influences professional practice around birth is also important, as this may positively or negatively impact the information that is provided to expectant parents.